Supervisory Strategies in Improving Quality of School Principals and Teachers at SMA Negeri 10 Tanjung Jabung Barat Jambi Province - Winarno, Winarno; Muspawi, Mohamad (Mudir : Jurnal Manajemen Pendidikan, 2024)
All stakeholders in educational institutions, principals and teachers while at school must create a better leadership and learning process. However, sometimes there are school principals and teachers who are not active or proactive in improving their quality. Therefore, improving the quality of school principals and teachers is very important which is influenced by several variables, including supervisory strategies. Based on these problems, the author conducted research on supervisors' strategies in improving the quality of principals and teachers at SMA Negeri 10 Tanjung Jabung Barat Jambi. This research aims to identify improvements in the quality of principals and teachers at SMA Negeri 10 Tanjung Jabung Barat Jambi. The principal and deputy principal and teachers were the respondents in this research. This research methodology combines qualitative and descriptive approaches. Information is collected by means of observation, discussion and documentation. The findings of this research show that the supervisor's strategy for improving the quality of Principals at SMA Negeri 10 Tanjung Jabung Barat is through monthly meetings to review quality, discipline and politeness, active MGMP forums, and training to improve quality. Supervisors' strategies for improving the quality of teachers at SMA Negeri 10 Tanjung Jabung Barat, through qualification indicators, personality competence, learning competence and social competence.